2020
DOI: 10.1101/2020.10.16.342824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coexistence holes characterize the assembly and disassembly of multispecies systems

Abstract: A central goal of life science has been to understand the limits of species coexistence. However, we know surprisingly little about the structure of species coexistence below such limits, and how it affects the assembly and disassembly of ecological systems. Here we introduce a novel hypergraph-based formalism that fully captures the structure of coexistence in multispecies systems. Our formalism uncovers that, below its limits, coexistence in ecological systems has ubiquitous discontinuities that we call "coe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Though not as widely recognized, three other outcomes are also possible in 2-species competition: (IV) two species eventually coexist despite requiring a specific arrival order; (V) only one species survives or two species coexist depending on who arrives first; and (VI) the species that arrives late always replaces the species that arrives early. The presence of these other possibilities has been supported by empirical evidence (Drake, 1991;Warren et al, 2003;Amor et al, 2020;Angulo et al, 2020). Of these six scenarios, (III), (V) and (VI) all represent priority effects.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Though not as widely recognized, three other outcomes are also possible in 2-species competition: (IV) two species eventually coexist despite requiring a specific arrival order; (V) only one species survives or two species coexist depending on who arrives first; and (VI) the species that arrives late always replaces the species that arrives early. The presence of these other possibilities has been supported by empirical evidence (Drake, 1991;Warren et al, 2003;Amor et al, 2020;Angulo et al, 2020). Of these six scenarios, (III), (V) and (VI) all represent priority effects.…”
Section: Introductionmentioning
confidence: 78%
“…For example, let us focus on the persistent species combinations (i.e., knowing the nodes in assembly graphs). While a community with S species has 2 S ≠ 1 potential species combinations, it has been shown that only a small fraction of such combinations can persist (Angulo et al, 2020). Because of the sparsity of these persistent combinations, it can be possible to infer all persistent combinations using a minimum of S + 1 experiments in a community with S species (Maynard et al, 2020).…”
Section: From Theory To Testable Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Communities from two soil inocula were assembled in minimal media supplemented with one, two, or three carbon sources for 10 transfers (48 h each; Estrela et al, 2020a). Shown is the total number of families (left) and exact sequence variants (ESVs; right) in each of the self-assembled communities at transfer 10. sequential invasion of species (Angulo et al, 2020;Serván and Allesina, 2020). These theoretical studies have posed fascinating questions, such as whether top-down and bottom-up community assembly are fundamentally different from one another and posited the existence of coexistence holes and forbidden assembly paths that, violating the empirical assembly rule described above, could be present when communities are assembled from the bottom-up.…”
Section: Testing Ecological Hypotheses Under Well-controlled Conditionsmentioning
confidence: 99%